Republished research: Facilitated physical activity as a treatment for depressed adults: randomised controlled trial. Issue 10 (10th June 2013) - Chalder, Melanie; Wiles, Nicola J; Campbell, John; Hollinghurst, Sandra P; Haase, Anne M; Taylor, Adrian H; Fox, Kenneth R; Costelloe, Ceire; Searle, Aidan; Baxter, Helen; Winder, Rachel; Wright, Christine; et al.
Abstract : Study question: Does facilitated physical activity provide an effective treatment for adults with depression presenting in primary care? Summary answer: Although trial participants receiving the physical activity intervention in addition to usual care reported increased physical activity compared with those receiving usual care alone, there was no evidence to suggest that the intervention brought about any improvement in depressive symptoms or reduction in antidepressant use. What is known and what this paper adds: Numerous studies have reported the positive effects of physical activity, but most of the current evidence originates from small non-clinical samples using interventions that are not practicable in a healthcare setting. Our results indicate that offering patients a facilitated physical activity intervention is not an effective strategy for reducing symptoms of depression, although it increased self reported physical activity and sustained this effect over 12 months.